A new approach for disparity map determination (Daffodil International University Journal of Science and Technology, 2010)
This article presents a new method to determine disparity map useful for three-dimensional (3D) scene reconstruction. The main task behind the computation of disparity map is stereo correspondence matching. In recent years, several stereo matching algorithms have been developed to find corresponding pairs in two images: left and right images captured by a stereo camera. But these algorithms exhibit a very high computational cost. With a view to reduce the computation time and produce a smooth and detailed disparity map, a fast and new approach based on average disparity estimation is proposed in this research, which can tackle additive noise. Experimental results confirm that the method achieves a substantial gain in accuracy with less expense of computation time. Key Words: Disparity map, Stereo correspondence, Stereo Vision, 3D Scene Reconstruction. DOI: 10.3329/diujst.v4i1.4348 Daffodil International University Journal of Science and Technology Vol.4(1) 2009 pp.9-13